2012
DOI: 10.1136/emermed-2012-201730
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism rule-out criteria (PERC) in pulmonary embolism—revisited: A systematic review and meta-analysis

Abstract: ObjectivesTo perform a systematic review and meta-analysis including all the current studies to assess the accuracy of pulmonary embolism rule-out criteria (PERC) in ruling out pulmonary embolism (PE).MethodsWe conducted a comprehensive search of the major databases (Ovid Medline In-Process & Other Non-Indexed Citations, Ovid MEDLINE, Ovid EMBASE, Ovid PsycInfo, Ovid Cochrane Central Register of Controlled Trials, Ovid Cochrane Database of Systematic Reviews and Scopus) and references of potentially eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…A 2010 meta‐analysis found a pre‐test probability for aPE of 5.7% for low risk, 23.2% for intermediate risk and 49.3% for high risk. However, a definitive diagnosis still requires imaging (CTPA or V/Q scan) and most patients will require a D‐dimer or the PERC to ‘rule‐out’ a PE, given the 5.7% pre‐test probability in the low‐risk group (Fig. ).…”
Section: Diagnosis Of Suspected Pementioning
confidence: 99%
See 1 more Smart Citation
“…A 2010 meta‐analysis found a pre‐test probability for aPE of 5.7% for low risk, 23.2% for intermediate risk and 49.3% for high risk. However, a definitive diagnosis still requires imaging (CTPA or V/Q scan) and most patients will require a D‐dimer or the PERC to ‘rule‐out’ a PE, given the 5.7% pre‐test probability in the low‐risk group (Fig. ).…”
Section: Diagnosis Of Suspected Pementioning
confidence: 99%
“…If the PERC score is 0, the 45‐day VTE incidence is reported at <1% . A 2013 meta‐analysis further supported that PERC can confidently rule‐out PE in low probability patients …”
Section: Diagnosis Of Suspected Pementioning
confidence: 99%
“…Sensitivity of the tested alternative algorithm (PERC=0) to rule-out PE was 89% (64%–98%) and LR− was 0.52 (0.14–1.96), whereas a recent meta-analysis of 12 studies19 reported a pooled sensitivity of 97% (96%–98%) and an LR− of 0.17 (0.13–0.23). One explanation for the lower diagnostic accuracy of PERC in our study could be the smaller sample size of our study population compared with this meta-analysis where >14 000 patients were included.…”
Section: Discussionmentioning
confidence: 92%
“…Diagnostic algorithms utilizing clinical features such as the Wells criteria, PERC tool and sensitive D-dimer testing can be used to safely rule out PE in many low risk patients without the need for imaging [17]. A large meta-analysis of 12 studies showed that the overall proportion of missed PE's using the PERC tool was only 0.3% [18]. More recently, a randomized controlled trial also suggested that utilizing pretest probability to avoid imaging in low risk patients is both safe and cost-saving [19].…”
Section: Discussionmentioning
confidence: 99%